Profil pemahaman konsep siswa pada siswa kelas VII : materi aritmetika sosial - kristia, Dela; Absori, Mahmudi Nur (International Journal of Progressive Mathematics Education, 2024)
Purpose: This study aims to explore the conceptual understanding profiles of seventh-grade students in social arithmetic across varying mathematical ability levels to mitigate cognitive obstacles in numeracy literacy. Design/methodology/approach: An exploratory qualitative design with triangulation techniques was employed. Three subjects (high, middle, and low ability) were selected via purposive sampling. Instruments included problem-solving tests and clinical interviews based on NCTM indicators. Findings: High-ability students demonstrated coherent relational understanding. Middle-ability students exhibited sound verbal logic but suffered from dissociation in written symbolic representation. Low-ability students remained constrained by procedural fragmentation and contextual interpretation failures. Practical implications: Educators should implement professional noticing to bridge the transition from verbal to formal representation using guided discovery methods. Originality/value: This study provides a unique contribution by mapping specific cognitive gaps between oral articulation and written formalisation within social arithmetic.   Purpose: Penelitian ini bertujuan mengeksplorasi profil pemahaman konsep siswa kelas VII pada materi aritmetika sosial berdasarkan tingkat kemampuan matematis untuk memitigasi hambatan kognitif dalam literasi numerasi. Design/methodology/approach: Menggunakan desain kualitatif eksploratif dengan teknik triangulasi. Subjek terdiri dari tiga siswa (kemampuan tinggi, menengah, dan rendah) yang dipilih melalui purposive sampling. Instrumen meliputi tes pemecahan masalah dan wawancara klinis berdasarkan indikator NCTM. Findings: Siswa berkemampuan tinggi menunjukkan pemahaman relasional yang koheren. Siswa menengah memiliki logika verbal yang baik namun mengalami disosiasi pada representasi simbolik tertulis. Siswa berkemampuan rendah terjebak pada fragmentasi prosedural dan kegagalan interpretasi kontekstual. Practical implications: Guru harus menerapkan professional noticing untuk menjembatani transisi representasi verbal ke formal melalui metode guided discovery.Originality/value: Studi ini memberikan kontribusi unik melalui pemetaan gap kognitif spesifik antara kemampuan artikulasi lisan dan formalisasi tertulis dalam materi aritmetika sosial.